Transparent Conductive Film
Patent Information
- Application Number
- JP2023003120
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-30
- Filing Date
- 2023-01-12
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-05-31
AI Technical Summary
【0009】 本発明によれば、軽快な操作性および優れたペン摺動耐久性を有する透明導電性フィルムの提供が可能となる。
Smart Images

Figure 0007639836000005 
Figure 0007639836000006 
Figure 0007639836000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent conductive film having a transparent conductive film of indium-tin composite oxide laminated on a transparent plastic film substrate, and in particular to a transparent conductive film that has easy operability and excellent pen sliding durability when used in a resistive touch panel. [Background technology]
[0002] Transparent conductive films, which are made by laminating a transparent, low-resistance thin film onto a transparent plastic substrate, are widely used in electrical and electronic applications that utilize their electrical conductivity, such as in flat panel displays such as liquid crystal displays and electroluminescence (EL) displays, and as transparent electrodes in touch panels.
[0003] Resistive touch panels combine a fixed electrode made of a glass or plastic substrate coated with a transparent conductive thin film with a movable electrode (=film electrode) made of a plastic film coated with a transparent conductive thin film, and are used by overlapping them on the top of a display. Pressing the film electrode with a finger or pen, bringing the transparent conductive thin films of the fixed electrode and film electrode into contact, serves as input for the touch panel's position recognition. When inputting with a pen in particular, pen sliding durability is required. In addition, as capacitive touch panels have become more common in recent years, resistive touch panels are also required to be able to input data even with a light touch, just like capacitive touch panels. For example, people who have weak finger pressure or pen pressure due to age, illness, or other reasons will strongly require input data even with a light touch. However, in resistive touch panels, a certain amount of input load is required to press the film electrode with a finger or pen to bring the fixed electrode and the transparent conductive thin film of the film electrode into contact, so they do not have the light and smooth operation feel of capacitive touch panels. To solve these problems, there is a demand for transparent conductive films that are light and easy to operate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-071171 A Summary of the Invention [Problem to be solved by the invention]
[0005] The conventional transparent conductive film shown in Patent Document 1 attempts to improve pen sliding durability by controlling the crystallinity of the indium-tin composite oxide. However, when the input load test described below was carried out, the conventional transparent conductive film had insufficient operability.
[0006] In view of the above-mentioned problems in the prior art, an object of the present invention is to provide a transparent conductive film having easy operability and excellent pen sliding durability. [Means for solving the problem]
[0007] The present invention has been made in view of the above circumstances, and the transparent conductive film of the present invention, which is able to solve the above problems, has the following configuration. [1] A transparent conductive film of indium-tin composite oxide is laminated on at least one side of a biaxially oriented transparent PET film substrate; a curable resin layer containing an ultraviolet curable resin and one or more types of particles selected from inorganic particles and organic particles is formed on at least one surface of the laminate; The transparent conductive film has a thickness of the curable resin layer of 0.1 to 15 μm. [2] The transparent conductive film according to [1], wherein the curable resin layer is provided between the transparent conductive film and the biaxially oriented transparent PET film substrate. [3] The transparent conductive film according to [1] or [2], wherein the transparent conductive film has a thickness of 10 nm or more and 100 nm or less. [4] The transparent conductive film according to any one of [1] to [3], wherein the concentration of tin oxide contained in the transparent conductive film is from 0.5% by mass to 40% by mass. [5] The transparent conductive film according to any one of [1] to [4], further comprising a functional layer on the opposite side of the biaxially oriented transparent PET film substrate to the transparent conductive film. [6] The transparent conductive film according to any one of [1] to [5], which has an easy-adhesion layer on at least one side of the biaxially oriented transparent PET film substrate. [7] The transparent conductive film described in [6], wherein the easy-adhesion layer is disposed at at least one position between the biaxially oriented transparent PET film substrate and the curable resin layer, or between the biaxially oriented transparent PET film substrate and a functional layer. [8] The transparent conductive film according to any one of [1] to [7], wherein in an adhesion test on a surface of the transparent conductive film in accordance with JIS K5600-5-6:1999, a remaining area ratio of the transparent conductive film is 95% or more.
[0008] The transparent conductive film of the present invention has the following configuration. 1. A transparent conductive film having a transparent conductive film of indium-tin composite oxide laminated on at least one side of a transparent plastic film substrate, A transparent conductive film in which the input initial load of the transparent conductive film is 3 g or more and 15 g or less in the following input load test. (Input load test method) A transparent conductive film (size: 220 mm x 135 mm) is used as one of the panel plates, and the other panel plate is a transparent conductive thin film A consisting of an indium-tin composite oxide thin film (tin oxide content: 10 mass%) with a thickness of 20 nm deposited by sputtering on a glass substrate (size: 232 mm x 151 mm). On the transparent conductive thin film A side of a glass substrate with an indium-tin composite oxide thin film (hereinafter also referred to as ITO glass), epoxy resin (length 60 μm × width 60 μm × height 5 μm) is arranged in a square lattice with a pitch of 4 mm as a dot spacer. Next, starting from one of the four corners of the ITO glass, attach double-sided tape (thickness: 105 μm, width: 6 mm) to the transparent conductive thin film A side of the ITO glass so as to create a rectangle of 190 mm x 135 mm. Next, the transparent conductive film is attached with the transparent conductive layer B side on the double-sided tape attached to the ITO glass, and laminated so that the transparent conductive thin film A and the transparent conductive layer B face each other. At this time, one short side of the transparent conductive film is set to protrude from the ITO glass. Next, connect the ITO glass and the transparent conductive film with a tester. Next, a load is applied from the transparent conductive film side with a polyacetal pen (tip shape: 0.8 mmR), and the load value at which the resistance value measured by the tester stabilizes is defined as the input start load. The position where the load is applied with the pen is the central area surrounded by the four dot spacers, and the average value of the input start load at the three points is calculated. For example, it is preferable to measure the input starting load at three arbitrary points 50 mm or more away from the double-sided tape and take the average value. The decimal point may be rounded off. The position where the load is applied with the pen is the central region of the four dot spacers as shown in Fig. 6. In Fig. 6, the respective symbols indicate an ITO glass 10, a dot spacer 11, and a position 12 where the load is applied with the pen. 2. The transparent conductive film as described above, in which the bending resistance in the film bending resistance test described below is 0.23 N·cm or more and 0.90 N·cm or less, and further, the average maximum peak height described below of the conductive surface of the transparent conductive film satisfies the following formulas (2-1) and (2-2). (Film bending resistance test method) Take a 20 mm x 250 mm test piece from the transparent conductive film and place it on a horizontal stand with a smooth surface, with the transparent conductive layer facing up. At this time, only the 20 mm x 20 mm part of the test piece is placed on the horizontal stand, with the 20 mm x 230 mm part outside the horizontal stand. In addition, place a weight on the 20 mm x 20 mm part of the test piece. At this time, select the weight and size of the weight so that there is no gap between the test piece and the horizontal stand. Next, read the difference between the height of the horizontal table and the height of the tip of the film (hereinafter referred to as δ) on the scale, and then substitute the value into the following formula (1) to calculate the bending resistance. Equation (1) (g×a×b×L 4 )÷8δ (N cm) g = gravitational acceleration, a = length of the short side of the test piece, b = specific gravity of the test piece, L = length of the test piece, δ = difference in height between the horizontal table and the tip of the film (Average maximum mountain height rating) The average maximum peak height is the average of the maximum peak heights at five points. The five points are selected by first selecting one arbitrary point A. Next, two points are selected, one each 1 cm upstream and downstream of A in the longitudinal direction (MD) of the film. Next, two points are selected, one each 1 cm to the left and right of A in the transverse direction (TD) of the film. The maximum peak height is specified in ISO 25178, and was determined using a three-dimensional surface profiler, Bertscan (R5500H-M100, manufactured by Ryoka Systems Co., Ltd. (measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 10x)). Values less than 1 nm were rounded off. Equation (2-1) Average maximum peak height (μm) ≧ 4.7 × bending resistance -1.8 Formula (2-2) 0.005(μm)≦Average maximum peak height (μm)≦12.000(μm) 3. The maximum value of the maximum peak height in the average maximum peak height evaluation is more than 1.0 times and not more than 1.4 times the average maximum peak height, and The above transparent conductive film, wherein the minimum value of the maximum peak height in the average maximum peak height evaluation is 0.6 to 1.0 times the average maximum peak height. 4. The above transparent conductive film, wherein the transparent conductive film has a thickness of 10 to 100 nm. 5. The above transparent conductive film, wherein the concentration of tin oxide contained in the transparent conductive film is 0.5 to 40% by mass. 6. A curable resin layer is provided between the transparent conductive film and the transparent plastic film substrate. The above transparent conductive film further comprises a functional layer on the opposite side of the transparent plastic substrate to the transparent conductive film. 7. The above transparent conductive film having an easy-adhesion layer on at least one side of the transparent plastic film substrate. 8. The above transparent conductive film, wherein the easy-adhesion layer is disposed at at least one of the positions between the transparent plastic film substrate and the curable resin layer, or between the transparent plastic substrate and the functional layer. 9. The transparent conductive film described above, wherein the ON resistance of the transparent conductive layer of the transparent conductive film is 10 kΩ or less in the following pen sliding durability test. (Pen sliding durability test) A transparent conductive film is used as one panel plate, and a transparent conductive thin film made of a 20 nm thick indium-tin composite oxide thin film (tin oxide content: 10% by mass) is used as the other panel plate on a glass substrate by sputtering. The two panels are arranged with the transparent conductive thin films facing each other, with 30 μm diameter epoxy beads in between, to create a touch panel. Next, a 2.5 N load is applied to a polyacetal pen (tip shape: 0.8 mmR) and a linear sliding test is performed on the touch panel 50,000 times. The sliding distance at this time is 30 mm, and the sliding speed is 180 mm / sec. After this sliding durability test, the ON resistance (resistance value when the movable electrode (film electrode) and fixed electrode come into contact) is measured when the sliding part is pressed with a pen load of 0.8 N. 10. The transparent conductive film as described above, in which in an adhesion test based on JIS K5600-5-6:1999 on the surface of the transparent conductive film, the remaining area ratio of the transparent conductive film is 95% or more. Effect of the Invention
[0009] According to the present invention, it is possible to provide a transparent conductive film having easy operability and excellent pen sliding durability. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a schematic diagram for explaining the position of a center roll in an example of a sputtering device preferably used in the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing a configuration according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing a configuration according to one embodiment of the present invention. [Figure 4] FIG. 1 is a schematic diagram showing a configuration according to one embodiment of the present invention. [Diagram 5] FIG. 1 is a schematic diagram showing a configuration according to one embodiment of the present invention. [Figure 6] FIG. 2 is a schematic diagram illustrating measurement positions in an input load testing method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The transparent conductive film of the present invention is a transparent conductive film having a transparent conductive film of indium-tin composite oxide laminated on at least one side of a transparent plastic film substrate, and the input starting load of the transparent conductive film in the following input load test is 3 g or more and 15 g or less. (Input load test method) A transparent conductive film (size: 220 mm x 135 mm) is used as one of the panel plates, and the other panel plate is a transparent conductive thin film A consisting of an indium-tin composite oxide thin film (tin oxide content: 10 mass%) with a thickness of 20 nm deposited by sputtering on a glass substrate (size: 232 mm x 151 mm). On the transparent conductive thin film A side of a glass substrate with an indium-tin composite oxide thin film (hereinafter also referred to as ITO glass), epoxy resin (length 60 μm × width 60 μm × height 5 μm) is arranged in a square lattice with a pitch of 4 mm as a dot spacer. Next, starting from one of the four corners of the ITO glass, attach double-sided tape (thickness: 105 μm, width: 6 mm) to the transparent conductive thin film A side of the ITO glass so as to create a rectangle of 190 mm x 135 mm. Next, the transparent conductive film is attached with the transparent conductive layer B side on the double-sided tape attached to the ITO glass, and laminated so that the transparent conductive thin film A and the transparent conductive layer B face each other. At this time, one short side of the transparent conductive film is set to protrude from the ITO glass. Next, connect the ITO glass and the transparent conductive film with a tester. Next, a load is applied from the transparent conductive film side with a polyacetal pen (tip shape: 0.8 mmR), and the load value at which the resistance value measured by the tester stabilizes is defined as the input start load. The position where the load is applied with the pen is the central area surrounded by the four dot spacers, and the average value of the input start load at the three points is calculated. For example, it is preferable to measure the input starting load at three arbitrary points 50 mm or more away from the double-sided tape and take the average value. The decimal point may be rounded off. The position where the load is applied with the pen is the central region of the four dot spacers as shown in FIG.
[0012] Here, in the present invention, when the measurement is performed using a tester, it is preferable that the "stable resistance value" be determined when the resistance value fluctuates within a range of, for example, ±5%, depending on external factors such as the measurement environment.
[0013] The present invention having such characteristics makes it possible to provide a transparent conductive film having light operability and excellent pen sliding durability. The obtained transparent conductive film is extremely useful for applications such as resistive touch panels.
[0014] The transparent conductive film of the present invention has easy operability. It has been found that the transparent conductive film of indium-tin composite oxide having excellent operability has a maximum peak height on the surface on the transparent conductive film side that is within an appropriate range relative to the height of the dot spacers on the ITO glass for touch panels, has low bending resistance in a bending resistance test, and has a tin oxide concentration in the transparent conductive film close to the tin oxide concentration in the ITO glass for touch panels.
[0015] The light operability will be described. The light operability means that input to the resistive touch panel is possible even when the transparent conductive film side of the resistive touch panel is pressed lightly with a pen or a finger. In the present invention, the light operability was evaluated by an input load test. In the present invention, if the input start load of the transparent conductive film in the input load test is 3 g or more and 15 g or less, the transparent conductive film has light operability. The present invention, which has such an input start load, enables input by a light touch even for transparent conductive films used in applications such as resistive touch panels, for people who, due to age, illness, or other reasons, have weak finger pressure or writing pressure. An input start load of 15 g or less is preferable because it provides light operability. More preferably, it is 13 g or less. Even more preferably, it is 11 g or less. On the other hand, an input start load of 3 g or more is preferable because it prevents erroneous responses of the touch panel. More preferably, it is 5 g or more, and even more preferably, it is 8 g or more.
[0016] In the present invention, it is preferable that the bending resistance in the following film bending resistance test is 0.23 N·cm or more and 0.90 N·cm or less, and further that the average maximum peak height of the transparent conductive film on the transparent conductive layer side surface of the transparent conductive film satisfies the following formulas (2-1) and (2-2). First, we will explain the bending resistance measured by the film bending resistance test. In the film bending resistance test, the test piece is placed on a horizontal table with a smooth surface with the transparent conductive layer facing up. This is to align the direction in which the transparent conductive film deforms when pressed with a pen or finger from the non-transparent conductive layer side. Even for the same transparent conductive film, the bending resistance value changes depending on whether the transparent conductive layer is on the top or bottom in the film bending resistance test, so care must be taken when evaluating. In addition, when a curable resin layer is disposed between a transparent plastic substrate and a transparent conductive film, the thickness and hardness of the cured resin layer also affect the bending resistance. In addition, when curable resin layers are disposed on both sides of a transparent plastic substrate, the balance between the thickness and hardness of the cured resin layers on each side affects the bending resistance.
[0017] If the bending resistance of the transparent conductive film is 0.23 N·cm or more, the transparent conductive film is unlikely to deform when touched unintentionally with a very light force, so electrical contact is unlikely to occur between the transparent conductive film of the transparent conductive film and the transparent conductive film of the ITO glass for touch panels, which is preferable since it is easy to prevent erroneous input. It is also preferable because it has excellent pen sliding durability. It is more preferable that it is 0.27 N·cm or more. Even more preferable that it is 0.30 N·cm or more. On the other hand, if the bending resistance of the transparent conductive film is 0.90 N·cm or less, the transparent conductive film is easily deformed even when pressed from the transparent conductive film side with a pen or finger at a low input load, and the transparent conductive film of the transparent conductive film and the transparent conductive film of the ITO glass are easily electrically contacted, which is preferable for easy operability. It is more preferably 0.80 N·cm or less. It is even more preferably 0.70 N·cm or less. It is particularly preferably 0.60 N·cm or less.
[0018] (Film bending resistance test method) Take a 20 mm x 250 mm test piece from the transparent conductive film and place it on a horizontal stand with a smooth surface, with the transparent conductive layer facing up. At this time, only the 20 mm x 20 mm part of the test piece is placed on the horizontal stand, with the 20 mm x 230 mm part outside the horizontal stand. In addition, place a weight on the 20 mm x 20 mm part of the test piece. At this time, select the weight and size of the weight so that there is no gap between the test piece and the horizontal stand. Next, read the difference between the height of the horizontal table and the height of the tip of the film (= δ) on the scale, then substitute the value into the following formula (1) to calculate the bending resistance. Equation (1) (g×a×b×L 4 )÷8δ (N cm) g = gravitational acceleration, a = length of the short side of the test piece, b = specific gravity of the test piece, L = length of the test piece, δ = difference in height between the horizontal table and the tip of the film
[0019] In the present invention, when a film bending resistance test is performed, it is preferable that the bending resistance in the film bending resistance test is 0.23 N·cm or more and 0.90 N·cm or less, and further that the average maximum peak height of the transparent conductive film on the transparent conductive film side satisfies the following formulas (2-1) and (2-2). (Average maximum mountain height rating) The average maximum peak height is the average of the maximum peak heights at five points. The five points are selected by first selecting one arbitrary point A. Next, two points are selected, one each 1 cm upstream and downstream of A in the longitudinal direction (MD) of the film. Next, two points are selected, one each 1 cm to the left and right of A in the transverse direction (TD) of the film. The maximum peak height is specified in ISO 25178, and was determined using a three-dimensional surface profiler, Bertscan (R5500H-M100, manufactured by Ryoka Systems Co., Ltd. (measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 10x)). Values less than 1 nm were rounded off. Formula (2-1) Average maximum peak height ≧ 4.7 × bending resistance - 1.8 Formula (2-2) 0.005(μm)≦Average maximum peak height (μm)≦12.000(μm)
[0020] If the maximum peak height of the surface on the transparent conductive film side satisfies formulas (2-1) and (2-2), then even when pressed with a pen or finger from the transparent conductive film side with a low input load, electrical contact can be made between the transparent conductive film placed on the protrusions on the transparent conductive film side of the transparent conductive film and the transparent conductive film of the ITO glass for touch panels, which is preferable due to its light operability. More preferably, the y intercept of formula (2-1), i.e., the value shown by "-1.8" in formula (2-1) above, is -1.7 or more. Still more preferably, the y intercept of formula (2-1) is -1.6 or more. In addition, if the average maximum peak height is 0.005 (μm) or more, it is preferable because the transparent conductive film can be wound into a roll without any problems. More preferably, it is 0.010 (μm) or more. Even more preferably, it is 0.020 (μm) or more. In addition, if the average maximum peak height is 12,000 (μm) or less, unintended electrical contact between the transparent conductive film arranged on the protrusions on the transparent conductive film side of the transparent conductive film and the transparent conductive film of the ITO glass for touch panels is unlikely to occur, which is preferable because it is easy to prevent erroneous input. More preferably, it is 11,000 (μm) or less. Even more preferably, it is 10,000 (μm) or less. From the above, it was found that a suitable balance between the bending resistance and the average maximum peak height satisfies light operability and the like.
[0021] In the present invention, the maximum value of the maximum peak height in the average maximum peak height evaluation described below is more than 1.0 times and not more than 1.4 times the average maximum peak height, The minimum value of the maximum peak height in the average maximum peak height evaluation is 0.6 to 1.0 times the average maximum peak height. This range is preferable because it keeps the variation in the input start load to less than ±5%. If the minimum value of the maximum peak height in the average maximum peak height evaluation is 0.6 times or more of the average maximum peak height, the in-plane distribution of the high protrusions on the transparent conductive film side of the transparent conductive film, which contributes to light operability, is uniform, so that when pressing from the transparent conductive film side with a pen or finger, input to the touch panel is possible with the same input load at any location, which is preferable. It is more preferably 0.7 times or more. Even more preferably 0.8 times or more. On the other hand, if the maximum value of the maximum peak height in the average maximum peak height evaluation is 1.4 times or less of the average maximum peak height, the in-plane distribution of the high protrusions on the transparent conductive film side of the transparent conductive film, which contributes to light operability, is uniform, so that when pressing from the transparent conductive film side with a pen or finger, input to the touch panel is possible with the same input load at any location, which is preferable. It is more preferably 1.3 times or less. Even more preferably 1.2 times or less.
[0022] (Average maximum mountain height rating) The average maximum peak height is the average of the maximum peak heights at five points. The five points are selected by first selecting one arbitrary point A. Next, two points are selected, one each 1 cm upstream and downstream of A in the longitudinal direction (MD) of the film. Next, two points are selected, one each 1 cm to the left and right of A in the transverse direction (TD) of the film. The maximum peak height is specified in ISO 25178, and was determined using a three-dimensional surface profiler, Bertscan (R5500H-M100, manufactured by Ryoka Systems Co., Ltd. (measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 10x)). Values less than 1 nm were rounded off.
[0023] The transparent conductive film in the present invention is made of an indium-tin composite oxide. The surface resistance of the transparent conductive film of the present invention is preferably 50 to 900 Ω / □, more preferably 50 to 700 Ω / □. The total light transmittance of the transparent conductive film of the present invention is preferably 70 to 95%.
[0024] In the present invention, the thickness of the transparent conductive film is preferably 10 nm or more and 100 nm or less. When the thickness of the transparent conductive film is 10 nm or more, the transparent conductive film adheres to the entire transparent film substrate or the cured resin layer, and the film quality of the transparent conductive film is stable, so that the surface resistance value is stable and falls within a preferred range, which is preferable. More preferably, the thickness of the transparent conductive film is 13 nm or more, more preferably 16 nm or more. In addition, when the thickness of the transparent conductive film is 100 nm or less, the crystal grain size and crystallinity of the transparent conductive film are appropriate, and furthermore, the total light transmittance is at a practical level, which is preferable. More preferably, the thickness is 50 nm or less, even more preferably 30 nm or less, and particularly preferably 25 nm or less.
[0025] In the present invention, the tin oxide concentration contained in the transparent conductive film is preferably 0.5 to 40 mass%. It has been found that the closer the tin oxide concentration contained in the transparent conductive film of the transparent conductive film is to the tin oxide concentration contained in the ITO glass for touch panels, the easier the transparent conductive film of the transparent conductive film and the transparent conductive film of the ITO glass are to come into electrical contact, resulting in smoother operability. The tin oxide concentration contained in the ITO glass for touch panels is generally 10 mass%. In the present invention, when the difference between the tin oxide concentration contained in the transparent conductive film of the transparent conductive film and the tin oxide concentration contained in the ITO glass for a touch panel is 30 mass % or less, the transparent conductive film of the transparent conductive film and the transparent conductive film of the ITO glass are easily in electrical contact with each other, which is preferable in terms of easy operability. The tin oxide concentration in ITO glass for touch panels is often 10% by mass. Therefore, in the present invention, the tin oxide concentration in the transparent conductive film is preferably 40% by mass or less. More preferably, it is 25% by mass or less. Even more preferably, it is 20% by mass or less. Particularly preferably, it is 2% by mass or more and 18% by mass or more. Furthermore, if the tin oxide content is 0.5% by mass or more, the surface resistance of the transparent conductive film becomes a practical level, which is preferable. More preferably, the tin oxide content is 1% by mass or more, and particularly preferably, it is 2% by mass or more.
[0026] In one embodiment, the transparent conductive film of the present invention has a curable resin layer between the transparent conductive layer and the transparent plastic film substrate. Furthermore, it is preferable that the transparent plastic substrate has a functional layer on the side opposite to the transparent conductive film. As shown in an example configuration in FIG. 2, the device may have a transparent conductive film 5, a curable resin layer 6, a transparent plastic film substrate 7, and a functional layer 8 in this order. When the transparent conductive film is heated during the touch panel processing process, monomers and oligomers generated from the transparent plastic film substrate may precipitate on the transparent conductive film, which may impair the smooth operability of the touch panel. Therefore, it is preferable to have a curable resin layer between the transparent conductive film and the transparent plastic film substrate, since this can prevent monomers and oligomers from precipitating on the transparent conductive film.
[0027] Furthermore, since monomers and oligomers precipitated from the transparent plastic substrate may reduce the visibility of the transparent conductive film, it is preferable that the transparent plastic film substrate has a curable resin layer and a functional layer. Furthermore, by having the curable resin layer and the functional layer, the bending resistance of the transparent conductive film can be adjusted to a more preferred range in the present invention. The curable resin layer and the functional layer according to the present invention can more effectively exhibit various properties such as pen sliding durability, etc. In particular, in the present invention, by having the curable resin layer and the functional layer, the bending resistance of the transparent conductive film of the present invention can be adjusted, the input start load can be adjusted to a predetermined range, and excellent visibility can be achieved. Although not intended to be limited to any particular theory, in the present invention, by having both a curable resin layer and a functional layer, a light operation feel and more accurate input properties can be achieved in a resistive touch panel. In addition, by providing a curable resin layer on the transparent plastic film substrate, the adhesive strength of the transparent conductive film is increased and the force acting on the transparent conductive film can be dispersed, which is preferable since it suppresses cracking, peeling, wear, etc. of the transparent conductive film in a pen sliding durability test. In addition, by providing a functional layer on the transparent plastic film substrate, it is preferable since it is less susceptible to scratches caused by inputting with a pen or the like.
[0028] In one embodiment, the transparent conductive film of the present invention has an easy-adhesion layer laminated on at least one side of a transparent plastic film substrate. For example, the transparent conductive film of the present invention preferably includes an easy-adhesion layer between the transparent plastic film substrate and the curable resin layer, between the transparent plastic film substrate and the functional layer, or both. Configuration examples are shown in Figures 3, 4, and 5. In these figures, an easy-adhesion layer 9 is disposed. Other reference characters are the same as those in Figure 2. The presence of the easy-adhesion layer enables the curable resin layer and the functional layer to adhere firmly to the transparent plastic film substrate, and thus peeling of the curable resin layer and the functional layer due to external forces can be more effectively suppressed, which is preferable.
[0029] The transparent conductive film of the present invention is a transparent conductive film having a transparent conductive film of indium-tin composite oxide laminated on at least one surface of a transparent plastic film substrate, and it is preferable that the ON resistance of the transparent conductive film in the transparent conductive film is 10 kΩ or less in the pen sliding durability test described below. (Pen sliding durability test) The transparent conductive film according to the present invention was used as one panel plate, and a transparent conductive thin film made of an indium-tin composite oxide thin film (tin oxide content: 10% by mass) having a thickness of 20 nm was used as the other panel plate by sputtering on a glass substrate. The two panel plates were arranged with epoxy beads having a diameter of 30 μm so that the transparent conductive thin films faced each other, and the panel plate on the film side and the panel plate on the glass side were attached with a double-sided tape having a thickness of 170 μm to produce a touch panel. Next, a load of 2.5 N was applied to a polyacetal pen (tip shape: 0.8 mmR), and a linear sliding test of 50,000 reciprocations was performed on the touch panel. In this test, the load of the pen was applied to the transparent conductive film surface according to the present invention. The sliding distance at this time was 30 mm, and the sliding speed was 180 mm / sec. After this sliding durability test, the ON resistance (resistance value when the movable electrode (film electrode) and the fixed electrode contact each other) was measured when the sliding part was pressed with a pen load of 0.8 N.
[0030] In the present invention, if the ON resistance of the transparent conductive film of the transparent conductive film in the pen sliding durability test is 10 kΩ or less, it is preferable because cracks, peeling, wear, etc. are suppressed in the transparent conductive film even when continuous input is made to the touch panel with a pen. In one embodiment, the ON resistance may be 9.5 kΩ or less, more preferably 5 kΩ or less. For example, the ON resistance may be 3 kΩ or less, 1.5 kΩ or less, and preferably 1 kΩ or less. The ON resistance is, for example, 5 kΩ or more, may be 3 kΩ or more, and is preferably 0 kΩ or more. By keeping the ON resistance within this range, cracks, peeling, wear, etc. on the transparent conductive film are suppressed even when continuous input is made to the touch panel with a pen. In one embodiment, these upper and lower limits may be combined as appropriate.
[0031] For example, the transparent conductive film of the present invention has a remaining area ratio of 95% or more on the surface of the transparent conductive film in an adhesion test conforming to JIS K5600-5-6:1999. The transparent conductive film of the present invention preferably has a remaining area ratio of 95% or more even when an adhesion test (JIS K5600-5-6:1999) is performed on the transparent conductive film surface, more preferably, the peeled area of the transparent conductive film is 99% or more, and particularly preferably, 99.5% or more. Since the remaining area ratio of the transparent conductive film is within the above range in the adhesion test, the transparent conductive film is in close contact with the layer in contact with the transparent conductive film, such as the transparent plastic film substrate and the cured resin layer, so that even if the touch panel is continuously inputted with a pen, cracks, peeling, wear, etc. are suppressed, and further, even if a force stronger than that expected for normal use is applied, cracks, peeling, etc. are suppressed on the transparent conductive film, which is preferable.
[0032] For example, in the transparent conductive film of the present invention, the remaining area ratio of the functional layer on the surface of the functional layer is 95% or more in an adhesion test conforming to JIS K5600-5-6: 1999. In the transparent conductive film of the present invention, even when an adhesion test (JIS K5600-5-6: 1999) is performed on the functional layer surface, the remaining area ratio of the functional layer surface is preferably 95% or more, more preferably 99% or more, and particularly preferably 99.5% or more. Transparent conductive films whose functional layer does not peel off in adhesion tests are preferable because the functional layer is in close contact with the transparent plastic film substrate, thereby preventing appearance defects such as cracking, peeling, and wear of the functional layer even when continuous input is made to the touch panel with a pen; furthermore, even if a force stronger than expected in normal use is applied, the functional layer absorbs the force, preventing cracking, peeling, etc. of the transparent conductive film.
[0033] The manufacturing method for obtaining the transparent conductive film of the present invention is not particularly limited, but for example, the following manufacturing method can be preferably exemplified. A sputtering method is preferably used as a method for forming a transparent conductive film of indium-tin composite oxide on at least one surface of a transparent plastic film substrate. In order to manufacture a transparent conductive film with high productivity, it is preferable to use a so-called roll-type sputtering device that supplies a film roll, and after film formation, winds it up into a film roll shape. A mass flow controller is used in the film formation atmosphere, inert gas and oxygen gas are flowed, a sintered target of indium-tin composite oxide is used, and the thickness of the transparent conductive film of indium-tin composite oxide is adjusted to 10 to 100 nm, and a transparent conductive film is formed on a transparent plastic film. In order to improve production efficiency, a plurality of sintered targets of indium-tin composite oxide may be placed in the direction of film flow. In addition, a mass flow controller may be used in the film formation atmosphere to flow a hydrogen atom-containing gas (hydrogen, ammonia, hydrogen + argon mixed gas, etc., as long as the gas contains hydrogen atoms, but water is excluded). It is known that if there is a lot of water in the film formation atmosphere, the quality of the transparent conductive film will be reduced, causing the surface resistance value to deviate from the desired range, or the transparent conductive film that should crystallize will not crystallize, adversely affecting the film quality of the transparent conductive film, so the amount of water in the film formation atmosphere is also an important factor. The median value (the midpoint between the maximum and minimum values) of the ratio of water pressure to the inert gas in the film formation atmosphere during sputtering on a film roll is set to 7.00 x 10 -3By controlling as follows, it is preferable because the deterioration of the film quality of the transparent conductive film can be suppressed. In order to control the amount of moisture in the film formation atmosphere, in addition to the rotary pump, turbo molecular pump, and cryopump that are often used as exhaust devices for sputtering machines, the following bombardment process, the limitation of the height difference of the unevenness of the end face of the film roll described below, and attaching a protective film with low water absorption rate to the opposite side of the surface on which the transparent conductive film is formed are preferable because the amount of moisture released from the film when forming the transparent conductive film is reduced. In addition, it is preferable to form the transparent conductive film on the transparent plastic film by setting the film temperature at 0°C or less during sputtering. The film temperature during film formation is substituted by the set temperature of the temperature regulator that adjusts the temperature of the center roll that the traveling film contacts. Here, FIG. 1 shows a schematic diagram of an example of a sputtering device that is preferably used in the present invention, in which the traveling film 1 is traveling in partial contact with the surface of the center roll 2. An indium-tin sputtering target 4 is installed via a chimney 3, and a thin film of indium-tin composite oxide is deposited and laminated on the surface of the film 1 traveling on the center roll 2. The temperature of the center roll 2 is controlled by a temperature regulator (not shown). If the film temperature is 0°C or lower, it is preferable because it can suppress the release of impurity gases such as water and organic gases from the film, which deteriorate the quality of the transparent conductive film. In addition, it is desirable to add oxygen gas during sputtering in order to bring the surface resistance and total light transmittance of the transparent conductive film to practical levels.
[0034] To control the moisture content when forming an indium-tin oxide film on a plastic film, it is preferable to actually observe the moisture content during film formation rather than observing the ultimate vacuum for the following two reasons.
[0035] The first reason is that when a film is formed on a plastic film by sputtering, the film is heated and moisture is released from the film, increasing the amount of moisture in the film-forming atmosphere and exceeding the amount of moisture measured when the ultimate vacuum is measured; therefore, it is more accurate to express this in terms of the amount of moisture at the time of film formation rather than in terms of the ultimate vacuum.
[0036] The second reason is the case of a device that inputs a large amount of transparent plastic film. In such a device, the film is input in the form of a film roll. When the film is rolled and input into a vacuum chamber, the outer layer of the roll is easy to remove water, but the inner layer of the roll is difficult to remove water. When the ultimate vacuum is measured, the film roll is stopped, but during film formation, the film roll runs, and the inner layer of the film roll, which contains a lot of water, is unwound, so the amount of moisture in the film formation atmosphere increases and is greater than the amount of moisture when the ultimate vacuum is measured. In the present invention, the amount of moisture in the film formation atmosphere can be controlled by observing the ratio of the moisture pressure to the inert gas in the film formation atmosphere during sputtering.
[0037] Before forming the transparent conductive film, it is desirable to pass the film through a bombardment process. The bombardment process is a process in which a voltage is applied to discharge and generate plasma while only an inert gas such as argon gas or a mixture of a reactive gas such as oxygen and an inert gas is flowing. Specifically, it is desirable to bombard the film by RF sputtering using a SUS target or the like. The bombardment process exposes the film to plasma, which releases water and organic components from the film, and the amount of water and organic components released from the film when the transparent conductive film is formed is reduced, which is desirable because it improves the film quality of the transparent conductive film. In addition, the bombardment process activates the layer that the transparent conductive film comes into contact with, which improves the adhesion of the transparent conductive film and therefore improves pen sliding durability.
[0038] In the film roll for forming the transparent conductive film, the height difference between the most convex and most concave points on the roll end face is preferably 10 mm or less. If it is 10 mm or less, water and organic components are less likely to be released from the film end face when the film roll is inserted into a sputtering device, which is preferable because it improves the quality of the transparent conductive film.
[0039] In a film (transparent plastic film substrate) on which a transparent conductive film is formed, it is desirable to apply a protective film with low water absorption to the surface opposite to the surface on which the transparent conductive film is formed. By applying a protective film with low water absorption, gas such as water is less likely to be released from the film substrate, which is preferable because it improves the quality of the transparent conductive film. As a substrate for a protective film with low water absorption, polyethylene, polypropylene, cycloolefin, etc. are preferable.
[0040] In the method for forming a transparent conductive film of crystalline indium-tin composite oxide on at least one surface of a transparent plastic film substrate, it is preferable to introduce oxygen gas during sputtering. When oxygen gas is introduced during sputtering, there is no problem due to oxygen deficiency in the transparent conductive film of indium-tin composite oxide, and the surface resistance of the transparent conductive film is low and the total light transmittance is high, which is preferable. Therefore, in order to make the surface resistance and total light transmittance of the transparent conductive film practical levels, it is preferable to introduce oxygen gas during sputtering. The total light transmittance of the transparent conductive film of the present invention is preferably 70 to 95%.
[0041] The transparent conductive film of the present invention is preferably obtained by forming a transparent conductive film of indium-tin composite oxide on a transparent plastic film substrate and then performing a heat treatment at 80 to 200°C for 0.1 to 12 hours in an oxygen-containing atmosphere after the transparent conductive film is laminated. A temperature of 80°C or higher is preferred when it is necessary to increase the crystallinity of the transparent conductive film in order to improve the pen sliding durability. A temperature of 200°C or lower is preferred because the flatness of the transparent plastic film is ensured.
[0042] <Transparent plastic film substrate> The transparent plastic film substrate used in the present invention is a film obtained by melt-extruding or solution-extruding an organic polymer into a film shape, and then stretching, cooling, and heat-setting the film in the longitudinal and / or transverse directions as necessary. Examples of the organic polymer include polyethylene, polypropylene, polyethylene terephthalate, polyethylene-2,6-naphthalate, polypropylene terephthalate, polybutylene terephthalate, nylon 6, nylon 4, nylon 66, nylon 12, polyimide, polyamideimide, polyethersulfane, polyetheretherketone, polycarbonate, polyarylate, cellulose propionate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyetherimide, polyphenylene sulfide, polyphenylene oxide, polystyrene, syndiotactic polystyrene, and norbornene-based polymers.
[0043] Among these organic polymers, preferred are polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, syndiotactic polystyrene, norbornene-based polymers, polycarbonate, polyarylate, etc. Furthermore, these organic polymers may be copolymerized with small amounts of monomers of other organic polymers or blended with other organic polymers.
[0044] The transparent plastic film substrate used in the present invention may be subjected to a surface activation treatment such as corona discharge treatment, glow discharge treatment, flame treatment, ultraviolet irradiation treatment, electron beam irradiation treatment, or ozone treatment, as long as the object of the present invention is not impaired.
[0045] In the transparent conductive film of the present invention, the thickness of the transparent plastic film substrate is preferably in the range of 100 μm or more and 240 μm or less, more preferably 120 μm or more and 220 μm or less. When the thickness of the plastic film is 100 μm or more, mechanical strength is maintained, and deformation due to pen input is small particularly when used in a touch panel, and pen sliding durability is excellent, which is preferable. On the other hand, when the thickness is 240 μm or less, light operability is maintained when used in a touch panel, which is preferable.
[0046] When a curable resin layer is laminated on a transparent plastic film substrate, it is possible to block the deposition of monomers and oligomers generated from the transparent plastic film substrate on the transparent conductive film, which is preferable since it does not impair the light operability of the touch panel. In addition, it is preferable since the transparent conductive film adheres strongly to the curable resin layer and the force applied to the transparent conductive film can be dispersed, which suppresses cracks, peeling, wear, etc. of the transparent conductive film in the pen sliding durability test. In order to improve the adhesion between the transparent plastic film substrate and the curable resin layer, it is preferable to provide an easy-adhesion layer between the transparent plastic film substrate and the curable resin layer.
[0047] By laminating a functional layer on the transparent plastic film substrate, it is possible to block the precipitation of monomers and oligomers generated from the transparent plastic film substrate, which is preferable since it suppresses the decrease in visibility of the transparent conductive film. It is preferable that the transparent plastic film substrate has a functional layer in order to adjust the bending resistance of the transparent conductive film. It is also preferable that the transparent plastic film substrate has a functional layer since it is less susceptible to scratches caused by inputting with a pen or the like.
[0048] The resin contained in the curable resin layer and the functional layer preferably used in the present invention is not particularly limited as long as it is a resin that is cured by application of energy such as heating, ultraviolet irradiation, electron beam irradiation, etc., and examples of the resin include silicone resin, acrylic resin, methacrylic resin, epoxy resin, melamine resin, polyester resin, urethane resin, etc. From the viewpoint of productivity, it is preferable to use an ultraviolet curable resin as the main component. The resin contained in the curable resin layer and the functional layer may be the same resin or different resins.
[0049] Examples of such ultraviolet-curable resins include polyfunctional acrylate resins such as acrylic acid or methacrylic acid esters of polyhydric alcohols, and polyfunctional urethane acrylate resins synthesized from diisocyanates, polyhydric alcohols, and hydroxyalkyl esters of acrylic acid or methacrylic acid, etc. If necessary, these polyfunctional resins can be copolymerized by adding monofunctional monomers such as vinylpyrrolidone, methyl methacrylate, and styrene.
[0050] In order to improve the adhesion between the transparent conductive thin film and the curable resin layer, it is effective to treat the surface of the curable resin layer by the following method. Specific methods include a discharge treatment method in which glow or corona discharge is irradiated to increase carbonyl groups, carboxyl groups, and hydroxyl groups, and a chemical treatment method in which acid or alkali is treated to increase polar groups such as amino groups, hydroxyl groups, and carbonyl groups.
[0051] The ultraviolet curing resin is usually used by adding a photopolymerization initiator. As the photopolymerization initiator, any known compound that absorbs ultraviolet light and generates radicals can be used without any particular limitation, and examples of such photopolymerization initiators include various benzoins, phenyl ketones, benzophenones, etc. The amount of the photopolymerization initiator added is usually 1 to 5 parts by mass per 100 parts by mass of the ultraviolet curing resin.
[0052] In the present invention, the curable resin layer and the functional layer preferably contain inorganic particles or organic particles in addition to the curable resin, which is the main component. By dispersing inorganic particles or organic particles in the curable resin, it is possible to form irregularities on the surfaces of the curable resin layer and the functional layer, thereby improving the surface roughness over a wide area. In the present invention, by improving the surface roughness of the curable resin layer, the bending resistance of the transparent conductive film can be adjusted to a more preferred range in the present invention, and various properties such as pen sliding durability, anti-Newton ring properties, and film winding properties can be more effectively exhibited. In the present invention, by improving the surface roughness of the functional layer, the bending resistance of the transparent conductive film can be adjusted to a more preferred range in the present invention, and various properties such as the winding property of the film, the writing comfort with a pen, and the tactile feel of the fingers can be more effectively exhibited.
[0053] Examples of the inorganic particles include silica, etc. Examples of the organic particles include polyester resin, polyolefin resin, polystyrene resin, polyamide resin, etc. The particles contained in the cured resin layer and the functional layer may be the same or different particles.
[0054] In addition to inorganic particles and organic particles, it is also preferable to use a resin incompatible with the curable resin in addition to the curable resin, which is the main component. By using a small amount of a resin incompatible with the curable resin of the matrix, phase separation occurs in the curable resin, and the incompatible resin can be dispersed in the form of particles. The dispersed particles of the incompatible resin can form unevenness on the surfaces of the curable resin layer and the functional layer, improving the surface roughness over a wide area.
[0055] Examples of the incompatible resin include polyester resin, polyolefin resin, polystyrene resin, polyamide resin, and the like.
[0056] Here, as an example, the blending ratio when inorganic particles are used in the curable resin layer is shown. The inorganic particles are preferably 0.1 parts by mass or more and 30 parts by mass or less per 100 parts by mass of ultraviolet curable resin, more preferably 0.1 parts by mass or more and 25 parts by mass or less, and particularly preferably 0.1 parts by mass or more and 20 parts by mass or less. When the blending amount of the inorganic particles is 0.1 parts by mass or more and 30 parts by mass or less per 100 parts by mass of ultraviolet curable resin, the convex parts formed on the surface of the curable resin layer are not too small, and an effective average maximum peak height can be imparted, and the touch panel has light operability, and further, since the transparent conductive film has some surface protrusions, the film winding property can be maintained, which is preferable. In addition, when inorganic particles are used in the curable resin layer, the higher the blending ratio within the above range, the higher the average maximum peak height of the curable resin layer tends to be. Furthermore, when inorganic particles are used in the curable resin layer, a higher blending ratio thereof within the above range tends to increase the bending resistance of the transparent conductive film.
[0057] Here, as an example, the blending ratio when inorganic particles are used in the functional layer is shown below: It is preferable that the inorganic particles are 0.1 parts by mass or more and 60 parts by mass or less per 100 parts by mass of the ultraviolet curable resin. When inorganic particles are used in the functional layer, the higher the blending ratio within the above range, the lower the bending resistance of the transparent conductive film. When the blending amount of the inorganic particles is 0.1 parts by mass or more and 60 parts by mass or less per 100 parts by mass of the ultraviolet curing resin, the bending resistance of the transparent conductive film can be adjusted to an appropriate value according to the present invention, which is preferable. In addition, since surface protrusions can be formed on the functional layer within a range that does not impair the effects of the present invention, the film winding property can also be maintained, which is preferable.
[0058] The above-mentioned ultraviolet curable resin, photopolymerization initiator, and resin incompatible with inorganic particles, organic particles, and ultraviolet curable resin are dissolved in a common solvent to prepare a coating liquid. There is no particular limitation on the solvent used, and for example, alcohol-based solvents such as ethyl alcohol, isopropyl alcohol, etc., ester-based solvents such as ethyl acetate, butyl acetate, etc., ether-based solvents such as dibutyl ether, ethylene glycol monoethyl ether, etc., ketone-based solvents such as methyl isobutyl ketone, cyclohexanone, etc., aromatic hydrocarbon-based solvents such as toluene, xylene, solvent naphtha, etc., can be used alone or in combination.
[0059] The concentration of the resin component in the coating liquid (i.e., the solid content concentration) can be appropriately selected in consideration of the viscosity according to the coating method. For example, the total amount of the ultraviolet curable resin, the photopolymerization initiator, and the high molecular weight polyester resin in the coating liquid is usually 20 to 80 mass %. The higher the concentration of the resin component, the higher the average maximum peak height of the curable resin layer tends to be. In addition, other known additives, such as a silicone-based leveling agent, may be added to this coating liquid as necessary.
[0060] In the present invention, the prepared coating solution is coated onto a transparent plastic film substrate. The coating method is not particularly limited, and any conventionally known method such as bar coating, gravure coating, or reverse coating can be used.
[0061] The coated coating liquid is dried in the next step, where the solvent is evaporated and removed. In this step, the high molecular weight polyester resin that was uniformly dissolved in the coating liquid becomes particles and precipitates in the UV-curable resin. After the coating is dried, the plastic film is irradiated with UV rays, causing the UV-curable resin to crosslink and harden, forming a hardened resin layer and a functional layer. In this hardening step, the particles of the high molecular weight polyester resin are fixed in the hard coat layer, and protrusions are formed on the surfaces of the hardened resin layer and the functional layer, improving surface roughness over a wide area.
[0062] The thickness of the curable resin layer is preferably in the range of 0.1 μm to 15 μm. More preferably, it is in the range of 0.5 μm to 10 μm, and particularly preferably, it is in the range of 1 μm to 8 μm. When the thickness of the curable resin layer is 0.1 μm or more, sufficient protrusions are formed, which is preferable. On the other hand, when the thickness is 15 μm or less, productivity is good, which is preferable. Furthermore, when the curable resin layer is thick, the bending resistance of the transparent conductive film tends to increase.
[0063] The thickness of the functional layer is preferably in the range of 0.1 μm to 15 μm. More preferably, it is in the range of 0.5 μm to 15 μm, and particularly preferably, it is in the range of 1 μm to 10 μm. If the functional layer is thick, it tends to reduce the bending resistance of the transparent conductive film. When the functional layer is 0.1 μm or more, sufficient protrusions are formed, which is preferable. On the other hand, if it is 15 μm or less, productivity is good and it is preferable.
[0064] With respect to the effects of the amounts of inorganic particles, organic particles, and immiscible resin contained in the curable resin layer, and the thickness of the curable resin layer, on the bending resistance of the transparent conductive film, the bending resistance of the transparent conductive film can be adjusted to the appropriate value described above by appropriately selecting the amounts of inorganic particles, organic particles, and immiscible resin contained in the functional layer, and the thickness of the functional layer. Therefore, in the present invention, the effect of the present invention cannot be obtained by simply providing a functional layer, but the characteristics of the present invention can effectively contribute to the bending resistance of the transparent conductive film.
[0065] In one embodiment, the thickness of the cured resin layer and the thickness of the functional layer may be the same. In another embodiment, for example, the absolute value of the difference between the thickness of the cured resin layer and the thickness of the functional layer has the following relationship: 0.1μm≦ |Thickness of cured resin layer - Thickness of functional layer|≦3μm In this way, in the present invention, by providing a difference in thickness between the cured resin layer and the functional layer, the bending resistance of the transparent conductive film can be adjusted to a more preferred range in the present invention. In addition, various properties such as pen sliding durability can be more effectively exhibited, and a transparent conductive film having easy operability can be obtained. In addition, it is preferable that the particle mass per unit volume of the cured resin layer and the particle mass per unit volume of the functional layer are different.
[0066] The adhesive layer according to the present invention is preferably formed from a composition containing a urethane resin, a crosslinking agent, and a polyester resin. As the crosslinking agent, a blocked isocyanate is preferable, a trifunctional or more blocked isocyanate is more preferable, and a tetrafunctional or more blocked isocyanate is particularly preferable. The thickness of the adhesive layer is preferably 0.001 μm or more and 2.00 μm or less.
[0067] In one aspect, the present invention provides a resistive touch panel having the transparent conductive film of the present invention. The touch panel may have known components in addition to the transparent conductive film of the present invention. The transparent conductive film for resistive touch panels of the present invention can provide the above-mentioned various effects in the touch panel. EXAMPLES
[0068] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Various measurements and evaluations in the examples were performed according to the following methods. (1) Total light transmittance The total light transmittance was measured using NDH-2000 manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS-K7361-1:1997.
[0069] (2) Surface resistance The measurement was performed by the four-terminal method in accordance with JIS-K7194:1994. The measurement device used was Lotesta AX MCP-T370 manufactured by Mitsubishi Chemical Analytech Co., Ltd.
[0070] (3) Average maximum mountain height evaluation The average maximum peak height is the average of the maximum peak heights at five points. The five points are selected by first selecting one arbitrary point A. Next, two points are selected, one each 1 cm upstream and downstream of A in the longitudinal direction (MD) of the film. Next, two points are selected, one each 1 cm to the left and right of A in the transverse direction (TD) of the film. The maximum peak height is specified in ISO 25178, and was determined using a three-dimensional surface profiler, Bertscan (R5500H-M100, manufactured by Ryoka Systems Co., Ltd. (measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 10x)). Values less than 1 nm were rounded off.
[0071] (4) Crystallinity of transparent conductive film A film sample with a transparent conductive thin film layer laminated thereon was cut into pieces measuring 1 mm x 10 mm, and attached to the top surface of a suitable resin block with the conductive thin film surface facing outward. After trimming, ultrathin sections roughly parallel to the film surface were prepared using a general ultramicrotome technique. The slice was observed under a transmission electron microscope (JEOL, JEM-2010) to select a surface area of the conductive thin film that was not significantly damaged, and photographed at an accelerating voltage of 200 kV and a direct magnification of 40,000 times. The crystallinity of the transparent conductive film was evaluated by observing the proportion of crystal grains under a transmission electron microscope, that is, the degree of crystallinity.
[0072] (5) Thickness of the transparent conductive film (film thickness) A film sample piece laminated with a transparent conductive thin film layer was cut into pieces measuring 1 mm x 10 mm and embedded in epoxy resin for electron microscopes. This was fixed to a sample holder of an ultramicrotome, and a thin cross-sectional slice parallel to the short side of the embedded sample piece was prepared. Next, a transmission electron microscope (JEOL, JEM-2010) was used to photograph a portion of the thin film of the slice that was not significantly damaged, at an accelerating voltage of 200 kV and a magnification of 10,000 times in bright field, and the film thickness was determined from the photograph obtained.
[0073] (6) Pen sliding durability test A transparent conductive film was used as one panel plate, and a transparent conductive thin film made of an indium-tin composite oxide thin film (tin oxide content: 10% by mass) with a thickness of 20 nm was used as the other panel plate by sputtering on a glass substrate. The two panels were arranged with epoxy beads of 30 μm in diameter interposed between them so that the transparent conductive thin films faced each other, to fabricate a touch panel. Next, a polyacetal pen (tip shape: 0.8 mmR) was applied with a load of 2.5 N, and a linear sliding test of 50,000 round trips was performed on the touch panel. The sliding distance at this time was 30 mm, and the sliding speed was 180 mm / sec. After this sliding durability test, the ON resistance (resistance value when the movable electrode (film electrode) and the fixed electrode contact each other) was measured when the sliding part was pressed with a pen load of 0.8 N. It is desirable that the ON resistance is 10 kΩ or less.
[0074] (7) Measurement of the tin oxide content in transparent conductive films Cut the sample (approximately 15 cm 2 ) into a quartz Erlenmeyer flask, 20 ml of 6 mol / l hydrochloric acid was added, and the flask was sealed with film to prevent the acid from volatilizing. The flask was left at room temperature for 9 days with occasional shaking to dissolve the transparent conductive film. The remaining film was removed, and the hydrochloric acid in which the transparent conductive film had dissolved was used as the measurement solution. The In and Sn in the solution were determined by the calibration curve method using an ICP emission spectrometer (manufacturer: Rigaku, model: CIROS-120 EOP). The measurement wavelength for each element was selected to be one with no interference and high sensitivity. The standard solutions were also prepared by diluting commercially available standard solutions of In and Sn.
[0075] (8) Input load test method A transparent conductive film (size: 220 mm x 135 mm) was used as one of the panel plates, and the other panel plate was a transparent conductive thin film A consisting of an indium-tin composite oxide thin film (tin oxide content: 10 mass%) with a thickness of 20 nm deposited by sputtering on a glass substrate (size: 232 mm x 151 mm). On the transparent conductive thin film A side of a glass substrate with an indium-tin composite oxide thin film (hereinafter also referred to as ITO glass), epoxy resin (60 μm length × 60 μm width × 5 μm height) was arranged in a square lattice pattern with a pitch of 4 mm as dot spacers. Next, double-sided tape (thickness: 105 μm, width: 6 mm) was attached to the transparent conductive thin film A side of the ITO glass so as to create a rectangle of 190 mm × 135 mm, starting from one of the four corners of the ITO glass. Next, the transparent conductive film is attached with the transparent conductive layer B side on the double-sided tape attached to the ITO glass, and laminated so that the transparent conductive thin film A and the transparent conductive layer B face each other. At this time, one short side of the transparent conductive film is set to protrude from the ITO glass. Next, connect the ITO glass and the transparent conductive film with a tester. Next, a load is applied from the transparent conductive film side with a polyacetal pen (tip shape: 0.8 mmR), and the load value at which the resistance value measured by the tester stabilizes is defined as the input start load. The position where the load is applied with the pen is the central area surrounded by the four dot spacers, and the average value of the input start load at the three points is calculated. The position where the load was applied with the pen was the central area of the four dot spacers as shown in Figure 6. The input start load was measured at three arbitrary points 50 mm or more away from the double-sided tape and the average value was calculated. The decimal point was rounded off.
[0076] (9) Film bending resistance test method A 20 mm x 250 mm test piece is taken from the transparent conductive film and placed on a horizontal stand with a smooth surface, with the transparent conductive layer facing up. Only the 20 mm x 20 mm part of the test piece is placed on the horizontal stand, with the 20 mm x 230 mm part outside the horizontal stand. A weight is also placed on the 20 mm x 20 mm part of the test piece. The weight and size of the weight are selected so that there is no gap between the test piece and the horizontal stand. Next, the difference between the height of the horizontal stand and the height of the tip of the film (= δ) is read on a scale. Next, the bending resistance is calculated by substituting the values into the following formula (1). Equation (1) (g×a×b×L 4 )÷8δ (N cm) g = gravitational acceleration, a = length of the short side of the test piece, b = specific gravity of the test piece, L = length of the test piece, δ = difference in height between the horizontal table and the tip of the film
[0077] (10) Evaluation of the maximum and minimum values of maximum peak height relative to the average maximum peak height Of the five maximum peak height values measured in the average maximum peak height evaluation, the maximum and minimum values are divided by the average maximum peak height.
[0078] (11) Adhesion test The test was carried out in accordance with JIS K5600-5-6:1999. The results in the table below show the adhesion as a percentage of the remaining area. The maximum percentage of the remaining area is 100%. The closer the percentage of the remaining area in the adhesion test in the table is to 100%, the smaller the peeled area is.
[0079] The transparent plastic film substrate used in the examples and comparative examples is a biaxially oriented transparent PET film (Toyobo Co., Ltd., A4380, thickness is shown in Tables 1 and 2) having an easy-adhesion layer on both sides. As the curable resin layer, silica particles (Nissan Chemical Co., Ltd., Snowtex ZL) were mixed in the amount shown in Tables 1 and 2 with 100 parts by mass of a photopolymerization initiator-containing acrylic resin (Dainichi Seika Chemical Industry Co., Ltd., Seikabeam (registered trademark) EXF-01J). A mixed solvent of toluene / MEK (8 / 2: mass ratio) was added as a solvent so that the solid content concentration was the value shown in Tables 1 and 2, and the mixture was stirred to dissolve uniformly to prepare a coating liquid (hereinafter, this coating liquid is referred to as coating liquid A). The coating liquid prepared was applied using a Mayer bar so that the thickness of the coating film was the value shown in Tables 1 and 2. After drying at 80°C for 1 minute, ultraviolet light was irradiated (light amount: 300 mJ / cm2) using an ultraviolet light irradiation device (I-Graphics Co., Ltd., UB042-5AM-W type). 2 ) and the coating was cured. Under the conditions shown in Tables 1 to 4, a functional layer was provided on the surface of the transparent plastic substrate opposite to the curable resin layer.
[0080] (Examples 1 to 7) Each example was carried out under the conditions shown in Table 1 as follows. Put the film into the vacuum chamber and measure 1.5×10 -4 The chamber was then evacuated to a vacuum of 0.6 Pa. Next, oxygen was introduced, followed by the introduction of argon as an inert gas to bring the total pressure to 0.6 Pa. 3W / cm for an indium-tin oxide composite sintered target or an indium oxide sintered target that does not contain tin oxide 2 A transparent conductive film was formed by DC magnetron sputtering. The film thickness was controlled by changing the speed at which the film passed over the target. The ratio of water pressure to inert gas in the film formation atmosphere during sputtering was measured using a gas analyzer (Transpector XPR3, manufactured by Inficon). In each example level, in order to adjust the ratio of water pressure to inert gas in the film formation atmosphere during sputtering, the presence or absence of a bombardment process, the unevenness height difference on the end surface of the film roll, and the temperature of the heating medium of the temperature regulator that controls the temperature of the center roll in contact with the film were adjusted as shown in Table 1. The temperature that is exactly in the middle between the maximum and minimum temperatures from the start of film formation on the film roll to the end of film formation is listed in Table 1 as the center value. The film on which the transparent conductive film was formed and laminated was subjected to the heat treatment shown in Table 1, and then the measurement was carried out. The measurement results are shown in Tables 1, 3 and 4.
[0081] (Comparative Examples 1 to 7) A transparent conductive film was produced and evaluated in the same manner as in Example 1 under the conditions shown in Table 2. The results are shown in Tables 2 to 4.
[0082] [Table 1]
[0083] [Table 2]
[0084] [Table 3]
[0085] [Table 4]
[0086] As shown in Tables 1 to 4, the transparent conductive films of Examples 1 to 7 have an input start load within the range of the present invention, and therefore have excellent light operability and pen sliding durability when used in a resistive touch panel, combining both properties. However, Comparative Examples 1 to 7 do not achieve both light operability and pen sliding durability. [Industrial Applicability]
[0087] As described above, according to the present invention, a transparent conductive film having easy operability and excellent pen sliding durability can be provided, which is extremely useful for applications such as resistive film touch panels. [Explanation of symbols]
[0088] 1. Film 2. Center roll 3. Chimney 4. Indium-tin oxide target 5. Transparent conductive film 6.Curing resin layer 7. Transparent plastic film substrate 8. Functional Layer 9.Easy adhesion layer 10.ITO glass 11. Dot Spacer 12. Position to apply load with pen
Claims
1. A transparent conductive film of indium-tin composite oxide is laminated on at least one surface of a biaxially oriented transparent PET film substrate, a curable resin layer containing an ultraviolet curable resin and one or more types of particles selected from inorganic particles and organic particles is formed on at least one surface of the biaxially oriented transparent PET film substrate; The thickness of the curable resin layer is 0.1 to 15 μm, The bending resistance of the film measured by the bending resistance test below is 0.23 N cm or more and 0.90 N cm or less, A transparent conductive film, the conductive surface of which has an average maximum peak height satisfying the following formulas (2-1) and (2-2): (Film bending resistance test method) A 20 mm x 250 mm test piece is taken from the transparent conductive film, and placed on a horizontal table with a smooth surface with the transparent conductive film facing up. At this time, only the 20 mm x 20 mm part of the test piece is placed on the horizontal table, and the 20 mm x 230 mm part is placed outside the horizontal table. In addition, a weight is placed on the 20 mm x 20 mm part of the test piece. At this time, the weight and size of the weight are selected so that there is no gap between the test piece and the horizontal table. Next, the difference between the height of the horizontal table and the height of the tip of the film, hereinafter referred to as δ, is read on the scale. Next, the bending resistance is calculated by substituting the numerical values into the following formula (1). Formula (1) (g×a×b×L 4 )÷8δ (N cm) g = gravitational acceleration, a = length of the short side of the test piece, b = specific gravity of the test piece, L = length of the test piece, δ = difference between the height of the horizontal table and the height of the tip of the film (Average maximum mountain height rating) The average maximum peak height is the average of the maximum peak heights of five points. The five points are selected by first selecting one arbitrary point A. Next, two points are selected, one each 1 cm upstream and downstream of A in the longitudinal (MD) direction of the film. Next, two points are selected, one each 1 cm to the left and right of A in the transverse (TD) direction of the film. The maximum peak height is specified in ISO 25178, and was determined using a three-dimensional surface profile measuring device Bertscan (Ryoka Systems, R5500H-M100 (measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 10x)). Values less than 1 nm were rounded off. Formula (2-1) Average maximum peak height (μm) ≧ 4.7 x bending resistance - 1.8 Formula (2-2) 0.005 (μm) ≦ Average maximum peak height (μm) ≦ 12.000 (μm)
2. The transparent conductive film according to claim 1 , wherein the curable resin layer is provided between the transparent conductive film and the biaxially oriented transparent PET film substrate.
3. 3. The transparent conductive film according to claim 1, wherein the transparent conductive film has a thickness of 10 nm or more and 100 nm or less.
4. 4. The transparent conductive film according to claim 1, wherein the concentration of tin oxide contained in the transparent conductive film is 0.5% by mass or more and 40% by mass or less.
5. The transparent conductive film according to any one of claims 1 to 4, further comprising a functional layer on the opposite side of the biaxially oriented transparent PET film substrate to the transparent conductive film.
6. The transparent conductive film according to any one of claims 1 to 5, further comprising an easy-adhesion layer on at least one side of the biaxially oriented transparent PET film substrate.
7. A transparent conductive film as described in claim 5, having an easy-adhesion layer at at least one position between the biaxially oriented transparent PET film substrate and the curable resin layer, or between the biaxially oriented transparent PET film substrate and the functional layer.
8. The transparent conductive film according to any one of claims 1 to 7, wherein a remaining area ratio of the transparent conductive film on a surface of the transparent conductive film is 95% or more in an adhesion test in accordance with JIS K5600-5-6:1999.
Citation Information
Patent Citations
Transparent conductive laminate for touch panel
JP2004071171A
Transparent conductor
JP2007012443A
Transparent conductive film, electrode plate for touch panel, and the touch panel
JP2007103348A
Transparent conductive film
JP2010080290A
Transparent conductive film, touch panel, and flexible display
JP2010225375A